The Influence of Parenting Patterns on Early Childhood Independence - Alini Haura Hazima; Lina Setiawati; Sayyidah Nafisa Mutmainah; Windi Listia Handayani; Ida Marito Nainggolan; Hafiziani Eka Putri; Euis Kurniati; Asep Kurnia Jayadinata (JURNAL PENA PAUD, 2026)
Based on field findings, the level of independence in early childhood aged 1-6 years is still low. Children often depend on the help of parents and teachers to perform simple activities such as eating, dressing, interacting with children of the same age, and the habit of parents who often wait for children at school. This study was conducted to identify the influence of parenting patterns on the independence of early childhood. The population in this study were parents who were actively involved in parenting and had early childhood children aged 3-5 years in several areas of West Java. The sample in this research was 44 people through a purposive sampling technique. The type of research conducted was quantitative research with multiple linear regression methods. The data collection technique in this study was through the use of an online g-form questionnaire. Based on data processing from SPSS version 25 calculations, the results obtained were an influence between parenting patterns and early childhood independence. The parenting pattern variable had a simultaneous impact of 16.3% on the early childhood independence variable, and the remaining 83.7% was influenced by other variables outside this study. The most influential parenting pattern is the democratic parenting pattern with a Sig value of 0.006 > 0.05, so it can be concluded that the democratic parenting pattern variable has a significant influence on the independence variable of early childhood.